Blended Learning: Solusi Model Pembelajaran Bahasa Arab - Ali, Jauhar; Baroroh, R. Umi; Andina Putri, Ajeng (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to determine the implementation and the advantages and disadvantages of the blended learning model in Arabic subjects in class VI SD Muhammadiyah 01 Kandang Panjang Pekalongan. The type of approach used is a qualitative approach. This type of research is field research (field research). The results of this study found that blended learning became a good learning model for its implementation in Arabic subjects at SD Muhammadiyah 01 Kandang Panjang, Pekalongan City during the covid-19 pandemic. The advantages of the blended learning model for Arabic subjects at SD Muhammadiyah 01 Kandang Panjang, Pekalongan City during the Covid-19 Pandemic include flexible learning, the use of good communication tools, and collaboration between teachers and guardians of students or teachers with learners. While the shortcomings are the lack of knowledge of teachers and students about learning technology and limited learning time.